Implementasi Peraturan Bupati Nomor 66 Tahun 2021 tentang Percepatan Pengembangan Nagari Wisata oleh Pemerintah Nagari di Nagari Ujung Gading Perspektif Siyasah Tanfidziyah - Elsy Humaaira; Hendri Hendri (Lembaga Yasin AlSys, 2026)
This study is motivated by the issuance of Regent Regulation (Peraturan Bupati) Number 66 of 2021 on the Acceleration of Nagari Tourism Development in Pasaman Barat Regency, which records 139 tourist attractions, two of which are located in Nagari Ujung Gading. Nevertheless, the tourist attractions in Nagari Ujung Gading tend to be left without optimal management and have not been utilized as they should. This study aims to analyze the implementation of Regent Regulation Number 66 of 2021 on the Acceleration of Nagari Tourism Development in Nagari Ujung Gading and to examine its management from the perspective of siyāsah tanfīẓiyyah, namely a branch of fiqh of statecraft that emphasizes the state’s duty to elaborate and implement legal products. The analysis focuses on the forms of tourism management carried out by the Nagari Ujung Gading Government and the extent to which these efforts reflect the implementation of the accelerated nagari tourism development policy in accordance with the mandate of the regent regulation. The findings reveal a gap between the regulatory norms and practice in the field, where the existing tourism potential has not been managed in a planned, sustainable manner that is aligned with the spirit of accelerated nagari tourism development. From the perspective of siyāsah tanfīẓiyyah, this condition indicates that the state’s obligations (regional government and nagari government) in operationalizing the established regulation to realize public welfare have not been optimally fulfilled. The study concludes that strengthening the role of the nagari government in the planning, management, and utilization of tourist attractions in a more systematic and accountable manner is crucial, in line with the principles of siyāsah tanfīẓiyyah that require effective and responsible implementation of the law to promote just and sustainable nagari tourism development.